Filaria associated clinical manifestations in children in an endemic area and morbidity control by immunomonitoring and optimal DEC therapy: Sevagram experience - Harinath, B. C. (Springer India, 2000)
Lymphatic filariasis is a major public health problem in India with 412 million people living in bancroftian endemic areas and is a major cause of clinical morbidity. Twenty million people are reported to suffer from chronic disease manifestations such as lymphoedema, hydrocele or elephantiasis. At least twice the number have been shown to suffer from acute and occult filarial infections in an endemic area without diagnosis. Due to non-availability of suitable diagnostic test for confirming filaria aetiology other than parasitological examination, no significant study on filariasis in children has been reported earlier. Studies in our laboratory for more than a decade showed usefulness of microfilarial excretory-secretory antigen in confirming filarial aetiology in acute and occult infections in adults as well as in children. This study reports acute and atypical manifestations such as lymphadenopathy, asthmatic bronchitis, pulmonary eosinophilia, mono-arthritis, recurrent URI, pneumonia, nutritional anemia, pain in abdomen etc. in children living in filaria endemic area having no microfilaraemia but showing filaria aetiology by immunomonitoring for the presence of antibody or antigen and responding to optimal DEC therapy.